Determination of Stability During First Impounding in Jatigede Earth Dam - Teuku Faisal Fathani; Anafi Minmahddun; Fikri Faris (Journal of Applied Geology, 2019)
The Jatigede Dam is a multi-purpose rockfill dam located in Sumedang Regency, West Java Province. The construction of the Jatigede Dam started in 2008 and it is the second largest dam in Indonesia after the Jatiluhur Dam. As one of the vital facilities, it is highly necessary to evaluate the stability of the Jatigede Dam to avoid dam collapse. First reservoir filling is one of the factors affecting the dam stability; therefore, this research aims to evaluate the Jatigede Dam stability during impounding. The transient seepage analysis was conducted to evaluate the pore pressure change during impounding. The result of seepage analysis was used to analyze the dam stability using the limit equilibrium method with Rockscience software of Slide2. The results of the seepage analysis shows that the rise of the reservoir water level affects the upstream slope stability. The safety factor of the upstream slope changes during the impounding process. All thesafety factors for the upstream and downstream slopes during impounding still meet theminimum safety factor criteria required.